Karakter Tanaman Kelor (Moringa oleifera Lam.) Aksesi Kabupaten Lombok Utara - Wahyu Risna Rianto; Sumarjan Sumarjan; Bambang Budi Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
The research aims to describe the morphological character and determine the genetic relationship among the Moringa oleifera Lam. accessions grown and develop in North Lombok Regency. The study was conducted in February-May 2017, using descriptive methods and direct surveys and purposive sampling with the observation sheets and questionnaires consisting of 38 accession samples. Data were analyzed using Hierarchical Cluster Analysis SPSS 16 program. The results shows that the closest gentic relationship was between Bayan-3 and Bayan-4 accessions with a coefficient value of 12.21 and the farthest between Pemenangr-1 and Gangga-2 accessions with coefficient values of 70.77. Among of the 38 accessions observed, it was divided into 8 groups, and at the phenon distance line 25 there was a merger between the Ganga-2 accessions and other accession groups. There was a close level of geetic relationship among the moringa plant accessions in North Lombok Regency.